Vulnerable Parkin Loss-of-Function Drosophila Dopaminergic Neurons Have Advanced Mitochondrial Aging, Mitochondrial Network Loss and Transiently Reduced Autophagosome Recruitment - Cackovic, Juliana; Gutierrez-Luke, Susana; Call, Gerald B.; Juba, Amber; O’Brien, Stephanie; Jun, Charles H.; Buhlman, Lori M. (Frontiers in Cellular Neuroscience, 2018)
Selective degeneration of substantia nigra dopaminergic (DA) neurons is a hallmark pathology of familial Parkinson’s disease (PD). While the mechanism of degeneration is elusive, abnormalities in mitochondrial function and turnover are strongly implicated. An Autosomal Recessive-Juvenile Parkinsonism (AR-JP) Drosophila melanogaster model exhibits DA neurodegeneration as well as aberrant mitochondrial dynamics and function. Disruptions in mitophagy have been observed in parkin loss-of-function models, and changes in mitochondrial respiration have been reported in patient fibroblasts. Whether loss of parkin causes selective DA neurodegeneration in vivo as a result of lost or decreased mitophagy is unknown. This study employs the use of fluorescent constructs expressed in Drosophila DA neurons that are functionally homologous to those of the mammalian substantia nigra. We provide evidence that degenerating DA neurons in parkin loss-of-function mutant flies have advanced mitochondrial aging, and that mitochondrial networks are fragmented and contain swollen organelles. We also found that mitophagy initiation is decreased in park (Drosophila parkin/PARK2 ortholog) homozygous mutants, but autophagosome formation is unaffected, and mitochondrial network volumes are decreased. As the fly ages, autophagosome recruitment becomes similar to control, while mitochondria continue to show signs of damage, and climbing deficits persist. Interestingly, aberrant mitochondrial morphology, aging and mitophagy initiation were not observed in DA neurons that do not degenerate. Our results suggest that parkin is important for mitochondrial homeostasis in vulnerable Drosophila DA neurons, and that loss of parkin-mediated mitophagy may play a role in degeneration of relevant DA neurons or motor deficits in this model.